Principal Leadership Strategies in Building Teachers’ Organizational Commitment - Delyani Delyani; Yasir Arafat; Rohana Rohana (Journal of Social Work and Science Education, 2027)
This study examines the principal’s leadership strategies in building teachers’ organizational commitment at SDN 148 Palembang. It focuses on the strategies implemented, the supporting and inhibiting conditions surrounding their implementation, and the solutions used to address persistent obstacles. A descriptive qualitative design was employed to understand leadership practices within the natural setting of the school. Six purposively selected informants participated: the principal, three teachers, one administrative staff member, and one school committee representative. Data were collected through semistructured interviews, moderate participant observation, and analysis of school documents. The data were reduced, organized, compared, and interpreted, while source and technique triangulation were used to strengthen credibility. The results show that the principal developed teacher commitment by continuously communicating the school vision, demonstrating discipline and responsibility, providing personal motivation and recognition, conducting developmental academic supervision, involving teachers in planning and decision making, and strengthening collaboration. These strategies increased teachers’ loyalty, discipline, responsibility, active participation, and sense of ownership. Supporting factors included an open communication climate, harmonious relationships, teacher competence, clear task distribution, administrative support, and cooperation from the committee and parents. The main barriers were uneven motivation, heavy administrative workloads, limited learning facilities, inefficient data systems, time pressure, and inconsistent parental participation. The principal addressed these issues through persuasive coaching, regular coordination, administrative digitalization, professional development, recognition, workload clarification, and stronger partnerships. The study highlights the importance of combining managerial direction with human-centered leadership to sustain teacher commitment in public elementary schools.